The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/aenm.201301953
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Photosystem I with Graphene Oxide for Photocurrent Enhancement

Abstract: matrixes, [ 5 ] the use of thick protein fi lms, [ 9 ] and the use of semiconductor electrode materials. [ 10,11 ] The integration of PSI with carbon nano-materials, however, has been limited. The work of Carmeli and co-workers demonstrated how PSI could be covalently attached to carbon nanotubes. [ 12 ] Additionally, our research group demonstrated how PSI could be interfaced as a monolayer on a graphene electrode. [ 13 ] The use of carbon nanostructures such as graphene and carbon nanotubes to develop nano-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 27 publications
1
33
1
Order By: Relevance
“…Taken together, these observations strongly suggest that the energy absorbed by PCP complexes, both at 405 nm and 640 nm, after being transferred between and within the pigments comprising the light-harvesting complex, is efficiently dissipated into the graphene layer. In general such effects can also be attributed to electron transfer from photosynthetic complex to graphene, as observed recently in [25]. However in this case a charge-separating complex, that is Photosystem I, was used and the whole structure was immersed in properly chosen electrolyte in order to facilitate the electron transfer.…”
mentioning
confidence: 99%
“…Taken together, these observations strongly suggest that the energy absorbed by PCP complexes, both at 405 nm and 640 nm, after being transferred between and within the pigments comprising the light-harvesting complex, is efficiently dissipated into the graphene layer. In general such effects can also be attributed to electron transfer from photosynthetic complex to graphene, as observed recently in [25]. However in this case a charge-separating complex, that is Photosystem I, was used and the whole structure was immersed in properly chosen electrolyte in order to facilitate the electron transfer.…”
mentioning
confidence: 99%
“…4c), which could be attributed to the basal activity of electrodes. In this regard, it has been recently shown that graphene display photocurrent in isolation 45,46 . Basal photocurrent also varied according to the electrolyte composition within the microampere range ( Fig.…”
Section: Functional Eeg-based Pec Devices Based On C Reinhardtii Ligmentioning
confidence: 99%
“…There are several promising concepts related to using different materials, which can act as transparent conducting electrodes, like graphene, TiO 2 or ITO [63,[69][70][71][72], and different complexes that perform light-harvesting, charge separation and charge transfer [4,8,9,16,28,29,73]. At the same time, plasmonic nanomaterials, like SIFs or nanowires, seem to be excellent structures for improving the performance of photosynthetic materials, not only in terms of enhancing the optical properties, but also their charge transfer properties, leading to increased photocurrent generation.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%